Mutations in the αIIb and β3 Genes that Cause Glanzmann Thrombasthenia Can Be Distinguished by a Simple Procedure Using Transformed B-Lymphocytes - Rosenberg, Nurit; Dardik, Rima; Rosenthal, Ester; Zivelin, Ariella; Seligsohn, Uri (Thrombosis and Haemostasis, 1998)
Glanzmann thrombasthenia (GT) is caused by a defect in either glycoprotein (GP) IIb (αIIb) or GPIIIa (β3) genes and therefore screening of both genes is required for mutation identification. The β subunit of the GPIIb/IIIa complex (β3) forms a complex with another α subunit (αv) yielding the αvβ3 vitronectin receptor (VnR). GT patients with mutations in the GPIIIa gene that cause diminished synthesis of GPIIIa are deficient in both GPIIb\IIIa and VnR, whereas patients with mutations in the GPIIb gene are deficient in GPIIb\IIIa, yet express normal or increased VnR in their platelets. The presence or absence of VnR in platelet membranes of GT patients has therefore been used for distinguishing between mutations in the GPIIb gene and mutations in the GPIIIa gene. However, the method of assessing VnR in platelets is cumbersome and use of fresh platelets is indispensible. In the present work we devised a procedure for detection of the VnR in B-lymphocytes transformed by Epstein-Bar virus (EBV). The transformed lymphocytes transcribed GPIIIa mRNA but not GPIIb mRNA and expressed VnR on their surface. Using flow cytometry analysis or immuno-precipitation and western blotting VnR was found in B-lymphocytes of GT patients bearing a well characterized mutation in the GPIIb gene. In contrast, in B-lymphocytes of GT patients bearing 2 different mutations in the GPIIIa gene no VnR was detectable. Thus, for determining which gene is mutated in a GT patient, EBV-transformed B-lymphocytes are useful and can as well be used for analyses of GPIIIa mRNA and genomic DNA. Ten ml of blood are sufficient for the procedure.